Design considerations for future radionuclide aerosol monitoring systems. (November 2019) - Miley, Harry S.; Burnett, Jonathan L.; Chepko, Ariane B.; Devoy, Clive L.; Eslinger, Paul W.; Forrester, Joel B.; Friese, Judah I.; Lidey, Lance S.; Morris, Scott J.; Schrom, Brian T.; Stokes, Sheldon; Swanwick, Michael E.; et al.
Abstract: Pacific Northwest National Laboratory (PNNL) staff developed the Radionuclide Aerosol Sampler Analyzer (RASA) for worldwide aerosol monitoring in the 1990s. Recently, researchers at PNNL and Creare, LLC, have investigated possibilities for how RASA could be improved, based on lessons learned from more than 15 years of continuous operation, including during the Fukushima Daiichi Nuclear Power Plant disaster. Key themes addressed in upgrade possibilities include having a modular approach to additional radionuclide measurements, optimizing the sampling/analyzing times to improve detection location capabilities, and reducing power consumption by using electrostatic collection versus classic filtration collection. These individual efforts have been made in a modular context that might constitute retrofits to the existing RASA, modular components that could improve a manual monitoring approach, or a completely new RASA. Substantial optimization of the detection and location capabilities of an aerosol network is possible and new missions could be addressed by including additional measurements. Highlights: Improved collection and measurement technology reviewed for legacy aerosol systems. New capabilities enable the verification responsibilities of aerosol systems in high-level release scenarios. Electrostatic precipitation improves sample air volume per watt. Simple MDC analysis shows existing systems could benefit from alternative operations. Shorter sampling intervals will enable better source location estimates.